Thermally conductive, flame retardant polycarbonate composition having a high comparative tracking index
A thermally conductive flame retardant polycarbonate composition, combining bisphenol A homopolycarbonate with talc, phosphorus-containing flame retardants, fluorine-containing antidrip agents, and anhydride-modified α-olefin polymers, addresses the low CTI and moderate flame retardancy of pure polycarbonate, achieving high CTI, V0 flame retardancy, and heat deformation resistance for high voltage applications.
Patent Information
- Application Number
- JP2024560587
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-14
- Filing Date
- 2023-04-06
- Publication Date
- 2025-04-16
AI Technical Summary
Polycarbonate materials have a low comparative tracking index (CTI) and moderate flame retardancy, making them unsuitable for high voltage applications in the electronic and electrical sector that require both high CTI and flame retardancy.
A thermally conductive flame retardant thermoplastic composition based on polycarbonate is developed, comprising at least 50% by weight of bisphenol A homopolycarbonate, 32% to 37% by weight of talc, 4% to 10% by weight of phosphorus-containing flame retardants, 0.3% to 2% by weight of fluorine-containing antidrip agents, and 1% to 3% by weight of anhydride-modified α-olefin polymers.
The composition achieves a high comparative tracking index of at least 400V, excellent flame retardancy classified as V0 according to UL94, and good heat deformation resistance with a Vicat softening temperature of at least 110°C, making it suitable for high voltage applications.
Smart Images

Figure 2025512094000001 
Figure 2025512094000002 
Figure 2025512094000003
Abstract
Description
[Technical field]
[0001] The present invention relates to thermally conductive, flame retardant thermoplastic compositions based on polycarbonate having a high comparative tracking index. [Background technology]
[0002] Polycarbonate offers many advantages over other thermoplastic polymers due to its high impact strength, high heat distortion resistance, and certain inherent flame retardancy. Due to this unique property profile, polycarbonate compositions are in principle suitable for a wide variety of applications, for example in the field of electrical and electronic components. In particular, good insulating properties and high flame retardancy are essential safety-related basic requirements for materials used in this field.
[0003] In applications where plastics are in direct contact with conductor tracks, a high resistance to tracking currents under voltage load is a prerequisite to ensure that there are no short circuits in the component and therefore no fires. Comparative Tracking Index (CTI) generally describes the resistance of plastic materials to environmental influences. The CTI value is a measure of the tendency of plastics to form conductive paths on the surface under voltage and promote the generation of electrical tracking currents under the influence of environmental influences, such as moisture and pollution. The higher the tracking current resistance of a material, i.e. the higher its Comparative Tracking Index (CTI value), the better it is suitable for use in high voltage applications, such as modern electromobility applications. Another advantage of materials with high CTI values is that it is possible to place conductor tracks close together in EE components without risk of short circuits, which in turn allows for a reduction in component dimensions and therefore a more compact design and weight reduction.
[0004] In contrast to other thermoplastic polymers, such as polystyrene, polyesters, etc., polycarbonate has a very low comparative tracking index and a moderate flame retardancy by itself. Due to the high proportion of aromatic structures, polycarbonate has a relatively high tendency to char. The CTI of pure polycarbonate is about 250 V or even lower (Non-Patent Document 1). However, for many applications in the electronic / electrical (EE) sector, such as the electromobility sector, a higher CTI is required for the materials used, for safety reasons. Therefore, polycarbonate has not been considered so far as a material for many applications that particularly require a high comparative tracking index of the material.
[0005] For applications requiring a high comparative tracking index of the material, the material must simultaneously have high flame retardancy, i.e. classification V0 according to UL94V, even at particularly low wall thicknesses.
[0006] Pure polycarbonate typically already has a certain inherent flame retardancy (classification V2 according to UL94V), which is insufficient for most applications in the EE sector. In order to achieve the required classification V0 according to UL94V, the addition of suitable flame retardants is required. Typically employed in polycarbonates are halogenated sulfonic acid compounds (e.g. Rimar salts (potassium perfluorobutanesulfonate, C4 salts) or KSS salts (potassium diphenylsulfone-3-sulfonate)), or also organophosphate compounds (e.g. bisphenol A bis(diphenylphosphate) (BDP), resorcinol bis(diphenylphosphate) (RDP)), or phosphazenes. The flame retardancy of polycarbonate can in principle be very well adjusted by adding suitable flame retardant additives. However, the mechanism of action of such flame retardants is based on the formation of a solid charred surface layer that blocks the oxygen supply and thus inhibits the combustion process.
[0007] For example, Patent Document 1 describes a thermally conductive polycarbonate-based composition containing 50% to 75% by weight of an aromatic polycarbonate, 15% to 35% by weight of talc, 0.5% to 3% by weight of an anhydride-modified α-olefin polymer, 0.4% to 0.6% by weight of a fluorine-containing anti-drip agent, 3% to 10% by weight of a phosphazene or 3% to 5% by weight of a phosphoric acid ester, and 3% to 10% by weight of barium sulfate present as a flame retardant synergist.
[0008] However, the effect that forms the basis of a good comparative tracking index is, inter alia, a low tendency to form conductive paths on the surface, which is the exact opposite of the "charring" mechanism of action of surfactant flame retardants and therefore poses a special challenge in achieving a high comparative tracking index and good flame retardancy in polycarbonate materials.
[0009] In the field of electronic or current-carrying components, there is a particular need for materials with a high comparative tracking index. Every current flow is accompanied by the generation of heat, which increases with increasing power. To ensure the life of such components by preventing technical failures, it is necessary to dissipate the generated heat sufficiently. It would be desirable to be able to provide polycarbonate materials that have a relatively high comparative tracking index and flame retardancy, and at the same time can also contribute to the dissipation of heat.
[0010] Thermally conductive polycarbonate materials are known in principle from the prior art. For example, US Pat. No. 5,399,433 describes corresponding compositions in which the thermal conductivity is improved by the use of talc. The basic polymer degradation caused by talc is largely suppressed by the addition of maleic anhydride modified olefin waxes, resulting in materials with advantageous mechanical properties. However, such materials do not have good flame retardancy, and the comparative tracking index is not significantly increased compared to pure polycarbonate. Up to now, experts have also been of the opinion that no polycarbonate materials with a high comparative tracking index exist so far.
[0011] The object was therefore to provide a thermally conductive polycarbonate-based composition, preferably specified according to the rapid test method according to IEC 60112:2009, with a high CTI of at least 400V, preferably at least 450V, preferably achieving UL94 classification V0 at 2 mm. The thermal conductivity (in-plane) is preferably at least 1.0 W / (mK), specified according to ASTM E 1461-13. Due to the field of application and heat development in EE parts, the composition should also preferably have a good heat distortion resistance, in particular a Vicat softening temperature, specified according to ISO 306:2014-3, VST method B, of at least 110°C, preferably at least 112°C, particularly preferably at least 115°C.
[0012] Surprisingly, it has been found that an improvement in the comparative tracking index can be achieved by the addition of talc, and the objective of providing a composition having the above complex property profile is achieved by combining an aromatic polycarbonate with talc, and a phosphorus-containing flame retardant, an anti-drip agent, and an anhydride modified α-olefin polymer, each in selected amount ranges. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] International Publication No. 2020 / 212245 [Patent Document 2] International Publication No. 2018 / 037037 [Non-patent literature]
[0014] [Non-Patent Document 1] F. Acquasanta et al., Polymer Degradation and Stability, 96 (2011), 2098-2103 Summary of the Invention [Problem to be solved by the invention]
[0015] Accordingly, the present invention provides a thermoplastic composition, the composition comprising: A) at least 50% by weight of bisphenol A homopolycarbonate; B) 32% to 37% by weight of talc; C) 4% by weight to 10% by weight of a phosphorus-containing flame retardant; D) 0.3% by weight to 2% by weight of a fluorine-containing drip prevention agent; E) 1 wt% to 3 wt% of an anhydride-modified α-olefin polymer; and does not contain any further fillers.
[0016] The composition according to the invention may contain, in addition to components A, B, C, D and E, further components, for example further additives, in the form of component F. The composition may also contain one or more further thermoplastics as blend partners (component G) which are different from the above-mentioned components and which are not included in any of components A to F. In the context of the present invention, unless expressly specified otherwise, the weight % values specified for components A, B, C, D, E, optionally component F and optionally component G, respectively, are based on the total weight of the composition. It will be understood that all components present in the composition according to the invention add up to 100% by weight. When a numerical range has an upper limit indicated by "~X", this also includes the specified numerical value and its upward rounding range.
[0017] Thermoplastic polymers which are suitable as blend partners apart from components A, E and F include, for example, further aromatic polycarbonates which are not bisphenol A homopolycarbonates, i.e. different from component A, polystyrene, styrene copolymers, aromatic polyesters such as polyethylene terephthalate (PET) or polybutylene terephthalate (PBT), PET-cyclohexanedimethanol copolymers (PETG), polyethylene naphthalate (PEN), PMMA and PMMA copolymers, PMMI, polyolefins such as polyethylene or polypropylene, as well as copolymers with styrene, for example transparent polystyrene-acrylonitrile (PSAN), or else also thermoplastic polyurethanes.
[0018] It is especially preferred when the above-mentioned compositions do not contain any additional components, but instead the amounts of component A, component B, component C, component D, component E, optionally component F and optionally component G, in particular in the preferred embodiments described, total 100% by weight, i.e. the composition according to the invention consists of component A, component B, component C, component D, component E, optionally component F and optionally component G, very preferably components A to F.
[0019] It is understood that the components used may contain typical impurities, such as impurities resulting from their manufacturing process. It is preferable to use components with the highest possible purity. Moreover, it is understood that such impurities may be present even in the event of comprehensive formulation of the composition.
[0020] The present invention also provides moldings made from the thermoplastic composition according to the invention, i.e. moldings that consist of the thermoplastic composition according to the invention or that contain regions made of the thermoplastic composition according to the invention. Such moldings are in particular moldings for which the above-mentioned property profile is particularly attractive, i.e. moldings that are part of components in the EE sector, in particular high-voltage switches, inverters, relays, electronic connectors, electrical connectors, circuit breakers, components for photovoltaic applications, electric motors, heat sinks, chargers and charging plugs for electric vehicles, electrical junction boxes, smart meter housings, miniature circuit breakers, busbars. The components are preferably designed for a working voltage of at least 400V. For this purpose, the materials advantageously used preferably have a comparative tracking index of at least 400V, in particular at least 450V, as specified above according to the rapid test method according to IEC 60112:2009.
[0021] The compositions according to the invention do not show any significant tracking current (more than 0.5 A for 2 seconds) even when subjected to at least 50 drops of 0.1% ammonium chloride solution at 400 V, more preferably at 450 V, preferably according to the rapid test method according to IEC 60112:2009 and described in the description section. The compositions according to the invention further have a flame retardancy according to UL94V of V0 with a test specimen thickness of 2 mm. In addition to a high CTI and good flame retardancy, the compositions preferably also have good heat distortion resistance, which is expressed by a Vicat softening temperature of at least 110°C, preferably at least 112°C, in particular 115°C, as specified according to ISO 306:2014-3, VST method B.
[0022] The individual components of the composition according to the invention are described in more detail hereinafter:
[0023] Ingredient A Component A of the thermoplastic composition according to the invention is a bisphenol A homopolycarbonate, ie an aromatic polycarbonate based on the sole monomeric unit bisphenol A.
[0024] The melt volume flow rate (MVR) of the aromatic bisphenol A homopolycarbonate used is specified in accordance with ISO 1133:2012-03 at a test temperature of 300°C and a load of 1.2 kg, preferably at 5 cm 3 / (10 minutes)~35cm 3 / (10 min), more preferably 6 cm 3 / (10 minutes)~21cm 3 / (10 min), particularly preferably 10 cm 3 / (10 minutes)~19cm 3 / (10 min), especially preferred 11 cm 3 / (10 minutes)~15cm 3 / (10 minutes).
[0025] The details of polycarbonate preparation have been described in numerous patent specifications over the past 40 years or so. In this specification, the following may be mentioned by way of example: Schnell, "Chemistry and Physics of Polycarbonates", Polymer Reviews, Volume 9, Interscience Publishers, New York, London, Sydney 1964, D. Freitag, U. Grigo, PR Mueller, H. Nouvertne, BAYER AG, "Polycarbonates" in Encyclopedia of Polymer Science and Engineering, Volume 11, Second Edition, 1988, pages 648-718, and finally U. Grigo, K. Kirchner and PR Mueller "Polycarbonate" [Polycarbonates] in Becker / Braun, Kunststoff-Handbuch [Plastics Handbook], volume 3 / 1, Polycarbonate, Polyacetale, Polyester, Celluloseester [Polycarbonates, Polyacetals, Polyesters, Cellulose Esters], Carl Hanser Verlag Munich, Vienna 1992, pages 117 to 299.
[0026] Aromatic polycarbonates are prepared, for example, by the interfacial process, by reaction of dihydroxyaryl compounds with carbonyl halides, preferably phosgene, and / or aromatic dicarbonyl dihalides, preferably benzene dicarbonyl dihalides, optionally using chain terminators and optionally using trifunctional or higher branching agents. Also possible is the preparation by reaction of dihydroxyaryl compounds with, for example, diphenyl carbonate, via melt polymerization methods.
[0027] In the case of bisphenol A homopolycarbonate, only bisphenol A is used as the dihydroxyaryl compound.
[0028] In the preparation of bisphenol A homopolycarbonates, suitable chain terminators are one or more linear or branched, preferably unsubstituted, C1-C 30 -alkyl radical-substituted or tert-butyl-substituted phenols. Particularly suitable chain terminators are phenol, cumylphenol, and / or p-tert-butylphenol. The amount of chain terminator used is preferably 0.1 mol% to 5 mol%, based on the moles of dihydroxyaryl compound used in each case. The chain terminator can be added before, during or after the reaction with the carbonic acid derivative.
[0029] In principle, the homopolycarbonates may also be branched.
[0030] Suitable branching agents are trifunctional or higher compounds known in polycarbonate chemistry, especially those having three or more phenolic OH groups.
[0031] Examples of suitable branching agents include 1,3,5-tri(4-hydroxyphenyl)benzene, 1,1,1-tri(4-hydroxyphenyl)ethane, tri(4-hydroxyphenyl)phenylmethane, 2,4-bis(4-hydroxyphenylisopropyl)phenol, 2,6-bis(2-hydroxy-5'-methylbenzyl)-4-methylphenol, 2-(4-hydroxyphenyl)-2-(2,4-dihydroxyphenyl)propane, tetra(4-hydroxyphenyl)methane, tetra(4-(4-hydroxyphenylisopropyl)phenoxy)methane, and 1,4-bis((4',4''-dihydroxytriphenyl)methyl)benzene, and 3,3-bis(3-methyl-4-hydroxyphenyl)-2-oxo-2,3-dihydroindole.
[0032] Whatever branching agent is used, its amount is preferably between 0.05 mol % and 2.00 mol %, based on the moles of bisphenol A used in each case.
[0033] The branching agent can either be an initial charge with the bisphenol A and the chain terminator in the aqueous alkaline phase or can be added dissolved in an organic solvent prior to phosgenation. In the case of the transesterification process, the branching agent is used together with the bisphenol A.
[0034] Further aromatic polycarbonates may in principle be present in the composition according to the invention as additional blend partners according to component G, provided that they do not negatively affect the desired property profile according to the invention of a high comparative tracking index and also good flame retardancy at 2 mm and do not reduce the Vicat temperature too drastically, i.e. preferably below the Vicat temperature of 110°C, preferably below 112°C, in particular below 115°C.
[0035] The thermoplastic composition according to the invention contains at least 50% by weight, preferably at least 54% by weight, of aromatic bisphenol A homopolycarbonate and is therefore based on aromatic polycarbonate.
[0036] Component B Talc in the context of the present invention is preferably a talc, or a mixture of talcs, of essentially the same chemical composition, particle size, porosity, and / or BET surface area.
[0037] Talc is a phyllosilicate with the general chemical composition Mg3[SiO 10 It can be described as magnesium silicate hydrate having the general formula [(OH)2]. However, different types of talc may deviate from this general composition as they contain different impurities.
[0038] The talc or talc mixture used for preparing the composition according to the invention may be sized or unsized. The talc is preferably unsized. In the context of the present invention, size is considered to be the controlled (chemisorption or physisorption) concentration of molecules on the surface. Thus, unsized talc is a talc that has not been surface-treated, i.e. after the talc particles with the desired particle size are collected and optionally subjected to compression, the talc is preferably not subjected to any further process steps that change the surface of the talc in a controlled manner by chemisorption and / or physisorption. However, this does not exclude that impurities, dust or similar particles may unintentionally reach part of the surface during further handling of the talc, as long as the surface of the talc does not lose its properties to a significant extent, especially in relation to pH.
[0039] Talc preferably has a pH of 8 to 10, particularly preferably 8.5 to 9.8, especially preferably 9.0 to 9.7, the pH being specified according to EN ISO 787-9:1995. It should be noted that EN ISO 787-9:1995 also refers to the option of adding ethanol or other organic solvents to improve the dispersion of the solid to be analyzed. According to the invention, preference is given to using only distilled water to specify the pH according to EN ISO 787-9:1995.
[0040] The talc component B preferably has a content of iron(II) oxide and / or iron(III) oxide of 0.2% to 2.5% by weight, particularly preferably 0.3% to 2.3% by weight, especially preferably 0.3% to 2.0% by weight. This content is preferably measured by X-ray fluorescence or atomic absorption spectroscopy. The content of iron oxide in the talc influences the degree of decomposition of polycarbonate. It is advantageous to use talc with a specified iron oxide content.
[0041] Component B also preferably has an aluminum oxide content of 0.01% to 0.5% by weight, particularly preferably 0.05% to 0.48% by weight and especially preferably 0.15% to 0.45% by weight.
[0042] Component B preferably has an average particle size D50 of 0.01 μm to 10 μm, particularly preferably 0.25 μm to 10.00 μm, even more preferably 0.5 μm to 10.00 μm, particularly preferably 1 μm to 5 μm, where the particle size D50 is determined by sedimentation analysis. The average D50 value is understood by the skilled person to mean the average particle size at which 50% of the particles are smaller than the stated value. The particle size D50 is preferably determined according to ISO13317-3:2001.
[0043] Component B is preferably 7.5 m 2 / g~20.0m 2 / g, particularly preferably 9.0m 2 / g~15.0m 2 / g, especially preferably 9.5m 2 / g~14.0m 2 / g. The determination of the surface area according to Brunauer, Emmett and Teller by gas adsorption is known per se to the person skilled in the art. The BET surface area is preferably determined according to ISO 4652:2012-06. This preferred BET surface area is particularly preferably related to the above-mentioned average particle size D50 of the talc. In the case of such a combination, it has been found that the component B used according to the invention is optimally matched to the component C used according to the invention. The specific acid number and molar mass of component E make it possible to minimize the decomposition of the polycarbonate caused by component B.
[0044] Particularly preferably, the talc has a talc content of more than 96% by weight, particularly preferably more than 97% by weight, especially preferably 98% by weight or more.
[0045] Likewise, the talc preferably has an ignition loss of 5.0% to 7.0% by weight, particularly preferably 5.2% to 6.5% by weight, and especially preferably 5.3% to 6.2% by weight at 1050° C. The ignition loss is preferably specified according to DIN 51081:2002.
[0046] The talc, which may also be a talc mixture from component B, is preferably in compressed form. In the case of a talc mixture, the abovementioned values are based on the entire talc mixture, i.e. component B, respectively.
[0047] The composition according to the present invention has a talc content of 32% to 37% by weight, preferably 34% to 36% by weight, particularly preferably 34.5% to 35.5% by weight, based on the total composition.
[0048] Component C Component C of the composition according to the invention is a phosphorus-containing flame retardant, which may be a single phosphorus-containing flame retardant or a mixture of different phosphorus-containing flame retardants.
[0049] Suitable phosphorus-containing flame retardants are cyclic phosphazenes, phosphorus compounds of formula (10), and mixtures thereof: TIFF2025512094000001.tif36170, R 1 , R 2 , R 3 , and R 4 are independently a C1-C8-alkyl radical, which in each case is optionally halogenated, in each case branched or unbranched, and / or a C5-C6-cycloalkyl radical, a C6-C 20 -aryl radical, or C7-C 12 - aralkyl radicals, which in each case are optionally substituted by branched or unbranched alkyl and / or halogen, preferably chlorine and / or bromine, n is independently 0 or 1; q is a value between 0 and 30; X is a monocyclic or polycyclic aromatic radical having 6 to 30 carbon atoms, or a straight or branched chain aliphatic radical having 2 to 30 carbon atoms, each of which can be substituted or unsubstituted and bridged or non-bridged.
[0050] Preferably, R 1 , R 2 , R 3 , and R 4 is independently branched or unbranched C1-C4-alkyl, phenyl, naphthyl, or C1-C4-alkyl substituted phenyl. 1 , R 2 , R 3 , and / or R 4 If they are radicals, these in turn can be substituted by halogens and / or alkyl groups, preferably chlorine, bromine and / or branched or unbranched C1-C4-alkyl. Particularly suitable aryl radicals are those corresponding to cresyl, phenyl, xylenyl, propylphenyl or butylphenyl, as well as their brominated and chlorinated derivatives.
[0051] X in formula (10) is preferably derived from a dihydroxyaryl compound.
[0052] X in formula (10) is particularly preferably the following: TIFF2025512094000002.tif56170 or their chlorinated and / or brominated derivatives. X (together with the adjacent oxygen atom) is preferably derived from hydroquinone, bisphenol A or diphenylphenol. It is likewise suitable that X is derived from resorcinol. Particularly preferably, X is derived from bisphenol A. n in formula (10) is preferably equal to 1. q is preferably 0 to 20, particularly preferably 0 to 10, and in the case of mixtures an average value of 0.8 to 5.0, preferably 1.0 to 3.0, further preferably 1.05 to 2.00, particularly preferably 1.08 to 1.60.
[0053] The phosphorus compound of the general formula (10) is preferably a compound of the formula (11), TIFF2025512094000003.tif43170 formula, R 1 , R 2 , R 3 , and R 4 are each independently a linear or branched C1-C8 alkyl radical and / or optionally a linear or branched alkyl substituted C5-C6 cycloalkyl radical, C6-C 10 -aryl radical, or C7-C 12 -aralkyl radical, n is independently 0 or 1; q is independently 0, 1, 2, 3, or 4; N is a number between 1 and 30, R 5 and R 6 are independently a linear or branched C1-C4-alkyl radical, preferably a methyl radical, Y is a linear or branched C1-C7 alkylidene, linear or branched C1-C7 alkylene radical, C5-C 12 -Cycloalkylene radical, C5-C 12 - a cycloalkylidene radical, -O-, -S-, -SO-, SO2, or -CO-.
[0054] Phosphorus compounds of formula (10) include, in particular, tributyl phosphate, triphenyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, octyl diphenyl phosphate, 2-ethyl cresyl diphenyl phosphate, tri(isopropylphenyl) phosphate, resorcinol bridged oligophosphate esters, and bisphenol A bridged oligophosphate esters. When phosphorus compounds of formula (10) are used, the use of oligomeric phosphate esters of formula (10) derived from bisphenol A is particularly preferred.
[0055] Further preference is given to the use of mixtures of the same structure but different chain lengths, in which case the q value specified is the average of the q values, determined by determining the composition (molecular weight distribution) of the mixture of phosphorus compounds by high pressure liquid chromatography (HPLC) in a mixture of acetonitrile and water (50:50) at 40°C and using this to calculate the average value of q.
[0056] Particularly preferably, bisphenol A-based oligophosphates according to formula (12) (bisphenol A bis(diphenyl phosphate)) with q=1 to 20, in particular q=1.0 to 1.2, are present in the composition according to the invention. TIFF2025512094000004.tif54170
[0057] Phosphorus compounds of this type are known (see, for example, EP-A-0 363 608, EP-A-0 640 655) or can be prepared in an analogous manner by known methods (see, for example, Ullmanns Enzyklopaedie der technischen Chemie [Ullmann's Encyclopedia of Industrial Chemistry], vol. 18, p. 301 ff., 1979; Houben-Weyl, Methoden der organischen Chemie [Methods of Organic Chemistry], vol. 12 / 1, p. 43; Beilstein vol. 6, p. 177).
[0058] Alternatively, it is particularly preferred to use as component C a cyclic phosphazene according to formula (13). TIFF2025512094000005.tif39170 formula, R is in each case the same or different, is an amine radical, in each case an optionally halogenated, preferably fluorohalogenated, more preferably monohalogenated, C1-C8-alkyl radical, preferably a methyl, ethyl, propyl or butyl radical, a C1-C8 alkoxy radical, preferably a methoxy, ethoxy, propoxy or butoxy radical, in each case optionally alkyl-substituted, preferably C1-C4-alkyl-substituted and / or halogen-substituted, preferably chlorine- and / or bromine-substituted, C5-C6-cycloalkyl radicals, In each case, optionally alkyl-substituted, preferably C1-C4-alkyl-substituted, and / or halogen-substituted, preferably chlorine, bromine, and / or hydroxy-substituted, C6-C 20 an aryloxy radical, preferably a phenoxy radical, a naphthyloxy radical, In each case, optionally alkyl-substituted, preferably C1-C4-alkyl-substituted, and / or halogen-substituted, preferably chlorine- and / or bromine-substituted, C7-C 12 - an aralkyl radical, preferably a phenyl-C1-C4-alkyl radical, or a halogen radical, preferably chlorine or fluorine, or is the OH radical, k is a natural number of 1 to 10, preferably 1 to 8, particularly preferably 1 to 5, and especially preferably 1.
[0059] Preferably used herein are commercially available phosphazenes, which are typically ring mixtures of different ring sizes.
[0060] Further preference is given to the following, either individually or in mixtures: propoxyphosphazenes, phenoxyphosphazenes, methylphenoxyphosphazenes, aminophosphazenes, fluoroalkylphosphazenes, and also phosphazenes having the following structure: TIFF2025512094000006.tif124170
[0061] In compounds 13a-13f shown above, k=1, 2, or 3.
[0062] Preferably, the proportion of phosphorus halogen substituted phosphazenes, for example those consisting of incompletely reacted starting materials, is less than 1000 ppm, more preferably less than 500 ppm.
[0063] The phosphazenes can be used alone or in mixtures. The radicals R can always be the same or two or more radicals in the formula can be different. The radicals R of the phosphazenes are preferably identical.
[0064] In one embodiment, only phosphazenes having the same R are used.
[0065] Preferably, the proportion of tetramers (k=2) is, based on component B, 2 mol % to 50 mol %, more preferably 5 mol % to 40 mol %, even more preferably 10 mol % to 30 mol %, particularly preferably 10 mol % to 22 mol %.
[0066] Preferably, the proportion of higher oligomeric phosphazenes (k=3, 4, 5, 6, and 7) is from 0 mol% to 30 mol%, more preferably from 2.5 mol% to 25 mol%, even more preferably from 5 mol% to 20 mol%, particularly preferably from 6 mol% to 15 mol%, based on component B.
[0067] Preferably, the proportion of oligomers with k≧8 is, based on component B, from 0 mol % to 2.0 mol %, preferably from 0.10 mol % to 1.00 mol %.
[0068] More preferably, the phosphazene of component C satisfies all three above conditions with respect to the proportion of oligomers.
[0069] Particularly preferably, phenoxyphosphazenes (all R=phenoxy, formula 13g) are present as component C, either alone or together with further phosphazenes according to formula (13) as component C, the proportion of oligomers with k=1 (hexaphenoxyphosphazenes) being 50 mol % to 98 mol %, particularly preferably 60% to 72% by weight, based on the amount of phenoxyphosphazene. If phenoxyphosphazenes are used, the proportion of oligomers with k=2 is especially preferably 15% to 22% by weight and those with k≧3 being 10% to 13% by weight. TIFF2025512094000007.tif53170
[0070] Alternatively, component C particularly preferably comprises a phenoxyphosphazene having a proportion of trimers (k=1) of 70 mol% to 85 mol%, a proportion of tetramers (k=2) of 10 mol% to 20 mol%, a proportion of higher oligomeric phosphazenes (k=3, 4, 5, 6, and 7) of 3 mol% to 8 mol%, and 0.1 mol% to 1 mol% of phosphazene oligomers with k≧8, based on component C, and particularly preferably such a phenoxyphosphazene.
[0071] In an alternative preferred embodiment, n is defined as the arithmetic mean of k, where n is in the range of 1.10 to 1.75, preferably 1.15 to 1.50, more preferably 1.20 to 1.45, and especially preferably 1.20 to 1.40 (including the range limits). TIFF2025512094000008.tif21170
[0072] Phosphazenes and their preparation are described, for example, in EP-A-728811, DE-A-1961668 and WO-A-97 / 40092.
[0073] The oligomer composition in each blend sample was determined after synthesis as follows: 31 Detection and quantification are possible by P NMR (chemical shifts; trimer δ: 6.5 ppm to 10.0 ppm; tetramer δ: -10 ppm to -13.5 ppm; higher oligomers δ: -16.5 ppm to -25.0 ppm).
[0074] Particularly preferably, component C comprises a bisphenol A-based oligophosphate ester according to formula (12) and / or a cyclic phosphazene according to formula (13), especially preferably component C is a bisphenol A-based oligophosphate ester according to formula (12) and / or a cyclic phosphazene according to formula (13), very particularly preferably component C is a cyclic phosphazene according to formula (13).
[0075] The content of the phosphorus-containing flame retardant in the composition according to the present invention is 4% by weight to 10% by weight, preferably 5% by weight to 8% by weight, particularly preferably 5.0% by weight to 8.0% by weight, based on the total composition.
[0076] The greater the amount of phosphorus-containing flame retardant used, the further the Vicat temperature is reduced. At amounts greater than 10% by weight, the Vicat temperature is reduced to such an extent that the inherently high heat resistance of polycarbonate makes the material unsuitable for applications in which polycarbonate can be used.
[0077] Component D The composition according to the invention contains a fluorine-containing anti-drip agent as component D, which may be a mixture of two or more anti-drip agents. The total amount of anti-drip agents (anti-drip agents) is 0.3% to 2% by weight, preferably 0.3% to 1.0% by weight, particularly preferably 0.4% to 0.7% by weight of at least one anti-drip agent, based on the entire composition.
[0078] The anti-drip agents used are preferably fluorine-containing polymers, especially polyolefins.
[0079] The fluorinated polyolefins preferentially used as anti-drip agents have a high molecular weight, a glass transition temperature above -30°C, generally above 100°C, and a fluorine content preferably between 65% and 76% by weight, in particular between 70% and 76% by weight. Suitable fluorinated polyolefins are polytetrafluoroethylene, polyvinylidene fluoride, tetrafluoroethylene / hexafluoropropylene copolymers, and ethylene / tetrafluoroethylene copolymers. Fluorinated polyolefins are known ("Vinyl and Related Polymers" by Schildknecht, John Wiley & Sons, Inc., New York, 1962, pages 484-494; "Fluoropolymers" by Wall, Wiley-Interscience, John Wiley & Sons, Inc., New York, volume 13, 1970, pages 623-654; "Modern Plastics Encyclopedia", 1970-1971, volume 47, No. 10 A, October 1970, McGraw-Hill, Inc., New York, pages 134 and 774; "Modern Plastics Encyclopedia", 1975-1976, October 1975, volume 52, No. 10 A, McGraw-Hill, Inc., New York, pages 27, 28 and (See U.S. Pat. Nos. 3,671,487, 3,723,373, and 3,838,092.) These can be prepared by known methods, for example, in an aqueous medium using a free radical forming catalyst (e.g., sodium peroxodisulfate, potassium peroxodisulfate, or ammonium peroxodisulfate, etc.) at a pressure of 7 kg / cm. 2 ~71kg / cm 2and polymerizing tetrafluoroethylene at a temperature of 0° C. to 200° C., preferably at a temperature of 20° C. to 100° C. Further details are described, for example, in US Pat. No. 2,393,967.
[0080] Depending on the application, the density of the fluorinated polyolefins is specified according to ISO 1183-1 (2019-09) to be 1.2 g / cm 3 ~2.3g / cm 3 , preferably 2.0 g / cm 3 ~2.3g / cm 3 The average particle size can be between 0.05 μm and 1000 μm as determined using optical microscopy or white light interferometry.
[0081] Suitable tetrafluoroethylene polymer powders are commercially available, for example, from DuPont under the trade name Teflon™.
[0082] Thus, particular preference is given to the use of polytetrafluoroethylene (PTFE), but the fluorine-containing anti-drip agent is also used in the form of a PTFE-containing composition. When a PTFE-containing composition is used as the fluorine-containing anti-drip agent, the minimum amount used is sufficient if the PTFE present in the entire composition is at least 0.2% by weight, preferably at least 0.21% by weight, particularly preferably at least 0.25% by weight. PTFE-containing compositions include Hostaflon™ TF2021 or PTFE blends, such as Blendex™ B449 from Chemtura (about 50% by weight PTFE and about 50% by weight SAN (derived from 80% by weight styrene and 20% by weight acrylonitrile)). Particular preference is given to the use of PTFE or a PTFE / SAN blend as the fluorine-containing anti-drip agent, and very particularly preferably the fluorine-containing anti-drip agent is PTFE or PTFE / SAN.
[0083] Component E Component E of the composition according to the invention is an anhydride-modified α-olefin polymer.
[0084] The α-olefin polymer is preferably based on at least one monomer selected from the group consisting of ethylene, 1-propene, 1-butene, 1-isobutene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-octadecene, 1-nonadecene, but may also be based on a mixture of these monomers. More preferably, the α-olefin polymer is based on at least one monomer selected from the group consisting of ethene, propene, 1-hexene, 1-octene. Particularly preferably, the α-olefin polymer is based on ethylene, propene and / or 1-octene.
[0085] In this context, "based on" means that preferably at least 90 wt. %, more preferably at least 95 wt. %, and especially preferably at least 98 wt. %, of the α-olefin polymers in the polycarbonate-containing composition, based on the total weight of the respective non-anhydride-modified α-olefin polymers, is formed from the respective monomer(s).
[0086] The α-olefin polymers are modified with anhydrides, the modification being carried out using unsaturated carboxylic acid anhydrides, preferably selected from the group consisting of maleic anhydride, phthalic anhydride, fumaric anhydride, itaconic anhydride and mixtures thereof, with particular preference given to maleic anhydride.
[0087] The anhydride modified α-olefin polymer is preferably free of styrene butadiene rubber, especially free of rubber.
[0088] Preferred anhydride modified α-olefin polymers are E1) 90.0% by weight to 99.5% by weight, preferably 92.0% by weight to 97.5% by weight, and more preferably 94.0% by weight to 97.0% by weight of an α-olefin polymer; E2) 0.5% to 10.0% by weight, more preferably 2.5% to 8.0% by weight, and even more preferably 3.0% to 6.0% by weight of an anhydride; Includes.
[0089] The olefin moiety E1) of the α-olefin polymers is particularly preferably The proportion of ethylene is 65.0% by weight to 96.0% by weight, more preferably 80.0% by weight to 96.0% by weight, and particularly preferably 84.0% by weight to 92.0% by weight; The proportion of propylene is 2.0% by weight to 10.0% by weight, particularly preferably 4.0% by weight to 8.0% by weight, The proportion of 1-octene is 2.0% by weight to 25.0% by weight, more preferably 2.0% by weight to 10.0% by weight, particularly preferably 4.0% by weight to 8.0% by weight; It is characterized by:
[0090] Especially preferably, the α-olefin polymers are not based on any further monomers.
[0091] Alternatively, the olefin portion C1) of the α-olefin polymer is particularly preferably based on propylene and / or ethylene, especially preferably to an extent of at least 98% by weight. Very preferably, the only monomer unit of the α-olefin polymer is propylene.
[0092] Average molecular weight M of anhydride-modified α-olefin polymers W is preferably 300 g / mol to 40,000 g / mol, more preferably 800 g / mol to 32,000 g / mol, even more preferably 1,000 g / mol to 22,000 g / mol, and particularly preferably 3,000 g / mol to 21,000 g / mol. W is determined by gel permeation chromatography at 150° C. in orthodichlorobenzene using polystyrene calibration, where the reported values are preferably average values from duplicate measurements.
[0093] The acid number of the anhydride modified α-olefin polymers is preferably at least 30 mg KOH / g, more preferably between 45 mg KOH / g and 170 mg KOH / g, and particularly preferably 100 mg KOH / g, as determined by potentiometric titration with alcoholic potassium hydroxide solution in accordance with DIN ISO 17025:2005-08.
[0094] Particularly preferably, the anhydride-modified α-olefin polymers according to component C are based on propene and modified with maleic anhydride, more preferably having an average molecular weight M of 1000 g / mol to 22000 g / mol, even more preferably 3000 g / mol to 21000 g / mol, as determined by gel permeation chromatography at 150° C. in orthodichlorobenzene using polystyrene calibration. w and an acid number, determined by potentiometric titration according to DIN ISO 17025:2005-08, of 45 mg KOH / g to 170 mg KOH / g, even more preferably of 50 mg KOH / g to 100 mg KOH / g.
[0095] The amount of the anhydride-modified α-olefin polymer in the entire composition is from 1 to 3% by weight, preferably from 1.2 to 2.5% by weight, more preferably from 1.3 to 2.3% by weight, particularly preferably from 1.4 to 2% by weight, and especially preferably 1.6% by weight.
[0096] Additional Additives (Component F) The polycarbonate compositions according to the present invention may contain one or more additional additives different from Component B, Component C, Component D, and Component E, which, when present, are collectively referred to as "Component F."
[0097] Other usual additives ("additional additives") are optionally present (0 wt%), preferably up to 10 wt%, even more preferably 0.1 wt% to 5 wt%, particularly preferably 0.1 wt% to 3 wt%, especially preferably 0.2 wt% to 1.0 wt%, these weight percentages being based on the total weight of the composition. The group of additional additives does not include any talc (component B) or any phosphorus-containing flame retardant according to component C. The group of additional additives does not include any fluorine-containing anti-drip agent, since this has already been described in component D. The group of additional additives also does not include any anhydride-modified α-olefin polymer according to component E.
[0098] Such further additives, as typically added to polycarbonates, are in particular heat stabilizers, antioxidants, release agents, UV absorbers, IR absorbers, impact modifiers, antistatic agents, flame retardants different from component C, optical brighteners, light scattering agents, hydrolysis stabilizers, transesterification stabilizers, (organic) dyes, (organic / inorganic) pigments, compatibilizers and / or laser marking additives, in amounts typical of polycarbonate-based compositions in particular. Such additives are described, for example, in EP-A-0839623, WO-A-96 / 15102, EP-A-0500496 or in "Plastics Additives Handbook", Hans Zweifel, 5th Edition 2000, Hanser Verlag, Munich. Such additives, which can be added individually or else as mixtures, are preferred additives according to the invention.
[0099] If additional additives are present after all, further preferred as additional additives are one or more additional additives selected from the group consisting of heat stabilizers, antioxidants, mold release agents, organic dyes, organic pigments, inorganic pigments. In particular, the proportion of additional additives is preferably 0% to 3% by weight. Particularly preferred as additional additives are at least one heat stabilizer, antioxidant, dye, pigment and / or mold release agent, especially preferred are heat stabilizers and / or pigments.
[0100] It will be understood that such additives can only be added in such amounts if they do not significantly negatively affect the effect according to the invention of high CTI and good flame retardancy, and preferably also do not reduce the Vicat temperature, as specified according to ISO 306:2014-3, VST method B, below 110° C., preferably below 115° C. It is therefore particularly preferred that in addition to the phosphorus-containing flame retardant according to component C, a further flame retardant is present in an amount of 0.05 wt.-% or less.
[0101] The composition according to the invention may indeed contain, in addition to component C, further flame retardants, but preferably not those selected from the group of alkali metal, alkaline earth metal or ammonium salts of aliphatic or aromatic sulfonic acid, sulfonamide or sulfonimide derivatives, and combinations thereof, "derivatives" being taken to mean compounds having a molecular structure in which, instead of a hydrogen atom or a functional group, a different atom or a different atomic group has been present, or in which one or more atoms / atoms have been removed, so that the parent compound is still recognizable.
[0102] Such flame retardants that are preferably not present in the composition according to the invention are in particular one or more compounds selected from the group consisting of sodium or potassium perfluorobutane sulfate, sodium or potassium perfluoromethanesulfonate, sodium or potassium perfluorooctane sulfate, sodium or potassium 2,5-dichlorobenzenesulfonate, sodium or potassium 2,4,5-trichlorobenzenesulfonate, sodium or potassium diphenylsulfonate, sodium or potassium 2-formylbenzenesulfonate, sodium or potassium (N-benzenesulfonyl)benzenesulfonamide, or mixtures thereof, among which sodium or potassium perfluorobutane sulfate, sodium or potassium perfluorooctane sulfate, sodium or potassium diphenylsulfonate, or mixtures thereof, in particular potassium perfluoro-1-butanesulfonate (which is commercially available, inter alia, as Bayowet® C4 from Lanxess, Leverkusen, Germany). It is particularly preferred that no further flame retardants are present at all.
[0103] Additives which are particularly preferably present are release agents, more preferably release agents based on fatty acid esters, even more preferably release agents based on stearic acid esters, very preferably release agents based on pentaerythritol. Particular preference is given to the use of pentaerythritol tetrastearate (PETS) and / or glycerol monostearate (GMS). If one or more release agents are used, their amount is preferably up to 1.0% by weight (inclusive), more preferably 0.01% to 0.7% by weight, particularly preferably 0.02% to 0.60% by weight, each based on the total composition.
[0104] An additive which is also particularly preferably present is a heat stabilizer, the amount of which is preferably up to 0.20% by weight, more preferably 0.01% to 0.10% by weight, even more preferably 0.01% to 0.05% by weight, particularly preferably 0.015% to 0.040% by weight, based on the total composition.
[0105] Suitable heat stabilizers are especially phosphorus-based stabilizers selected from the group of phosphates, phosphites, phosphonites, phosphines, and mixtures thereof.Examples include triphenyl phosphite, alkyl diphenyl phosphite, dialkyl phenyl phosphite, tris(nonylphenyl) phosphite, trilauryl phosphite, trioctadecyl phosphite, distearyl pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl) phosphite (Irgafos® 168), diisodecyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, bis(2,4-dicumylphenyl) pentaerythritol diphosphite (Do verphos(trademark) S-9228), bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, diisodecyloxypentaerythritol diphosphite, bis(2,4-di-tert-butyl-6-methylphenyl)pentaerythritol diphosphite, bis(2,4,6-tris(tert-butylphenyl)pentaerythritol diphosphite, tristearyl sorbitol triphosphite, tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, 6-isooctyl peroxy-2,4,8,10-tetra-tert-butyl-12H-dibenzo[d,g]-1,3,2-dioxaphosphocin, bis(2,4-di-tert-butyl-6-methylphenyl)methyl phosphite, bis(2,4-di-tert-butyl-6-methylphenyl)ethyl phosphite, 6-fluoro-2,4,8,10-tetra-tert-butyl-12-methyldibenzo[d,g]-1,3,2-dioxaphosphocin, 2,2',2''-nitrilo[triethyltris(3,3',5,5'-tetra-tert-butyl-1,1'-biphenyl 2-ethylhexyl (3,3',5,5'-tetra-tert-butyl-1,1'-biphenyl-2,2'-diyl) phosphite, 5-butyl-5-ethyl-2-(2,4,6-tri-tert-butylphenoxy)-1,3,2-dioxaphosphiran, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, triphenylphosphine (TPP), trialkylphenylphosphine, bisdiphenylphosphinoethane, or trinaphthylphosphine.These can be used alone or in mixtures, for example Irganox® B900 (a mixture of Irgafos® 168 and the antioxidant Irganox® 1076 in a 4:1 ratio) or a mixture of Doverphos® S-9228 with Irganox® B900 or Irganox® 1076. Particularly preferably, triphenylphosphine (TPP), Irgafos® 168, or tris(nonylphenyl)phosphite, or mixtures thereof, are used.
[0106] It is also possible to use phenolic antioxidants, such as alkylated monophenols, alkylated thioalkylphenols, hydroquinones and alkylated hydroquinones.Particular preference is given to using Irganox® 1010 (pentaerythritol 3-(4-hydroxy-3,5-di-tert-butylphenyl)propionate; CAS: 6683-19-8) and Irganox® 1076 (octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), preferably in an amount of 0.05% to 0.5% by weight.
[0107] It is also possible to add sulfonates or alkyl phosphates, such as mono-, di-, and / or trihexyl phosphate, triisooctyl phosphate, and / or trinonyl phosphate, as transesterification inhibitors. The alkyl phosphate used is preferably triisooctyl phosphate (tris-2-ethylhexyl phosphate). It is also possible to use mixtures of various mono-, di-, and / or trialkyl phosphates. Triisooctyl phosphate is preferably used in an amount of 0.003% to 0.05% by weight, more preferably 0.005% to 0.04% by weight, particularly preferably 0.01% to 0.03% by weight, based on the total composition.
[0108] Examples of impact modifiers are: core-shell polymers, such as ABS or MBS; olefin-acrylate copolymers, such as the Elvaloy™ variety from DuPont or the Paraloid™ variety from Dow; silicone acrylate rubbers, such as the Metablen™ variety from Mitsubishi Rayon Co., Ltd. The composition according to the present invention already has an exceptional property profile without additional impact modifiers. Therefore, the composition according to the present invention preferably does not contain impact modifiers.
[0109] The composition according to the invention does not contain, in addition to talc, any further fillers such as barium sulfate. Titanium dioxide is not considered here as a "filler" but rather an inorganic pigment according to component F.
[0110] When titanium dioxide is present, the composition according to the invention preferably contains from 0.1% to 2% by weight, preferably from 0.5% to 1.2% by weight of titanium dioxide.
[0111] The titanium dioxide of the composition according to the invention preferably has an average particle size D of 0.1 μm to 5 μm, preferably 0.2 μm to 0.5 μm, as determined by scanning electron microscopy (STEM). 50 However, titanium dioxide has different particle sizes, for example, average particle size D of 0.5 μm or more, for example 0.65 μm to 1.15 μm, as determined by scanning electron microscopy (STEM). 50
[0043]
[0112] The titanium dioxide preferably has a rutile structure.
[0113] The titanium dioxide used according to the invention is Ti(IV)O2, a white pigment. In addition to titanium, colored titanium dioxide also contains significant amounts of elements such as Sb, Ni, Cr, etc., to provide the impression of a color other than "white". It will be understood that trace amounts of other elements may be present as impurities in the titanium dioxide white pigment. However, these amounts are so small that the titanium dioxide does not result in any color tint.
[0114] Suitable titanium dioxide is preferably the titanium dioxide produced by the chloride process, hydrophobized, specially post-treated and suitable for use in polycarbonate.Instead of sized titanium dioxide, unsized titanium dioxide or a mixture of both can also be used in principle in the composition according to the invention.However, the use of sized titanium dioxide is preferred.
[0115] Possible surface modifications of titanium dioxide include inorganic and organic modifications. These include, for example, aluminum-based or polysiloxane-based surface modifications. Inorganic coatings can contain 0.0% to 5.0% by weight of silicon dioxide and / or aluminum oxide. Organic-based modifications can contain 0.0% to 3.0% by weight of a hydrophobic wetting agent. The titanium dioxide preferably has an oil absorption number, specified according to DIN EN ISO 787-5:1995-10, of 12 g to 18 g per 100 g titanium dioxide, more preferably 13 g to 17 g per 100 g titanium dioxide, particularly preferably 13.5 g to 15.5 g per 100 g titanium dioxide.
[0116] Particular preference is given to titanium dioxide having standard grade R2 according to DIN EN ISO 591-1:2001-08, stabilized with aluminum and / or silicon compounds and having a titanium dioxide content of at least 96.0% by weight. Such titanium dioxide is available under the trade names Kronos 2233 and Kronos 2230.
[0117] The polymer composition according to the invention, which contains in admixture component A, component B, component C, component D, component E and optionally component F, and optionally also further constituents, can be prepared using a powder premix. It is also possible to use a premix of pellet materials or pellet materials and powders together with the additives according to the invention. It is also possible to use a premix formed from a solution of the mixture of components in a suitable solvent, optionally followed by homogenization of the solution and removal of the solvent. In particular, the additives and further constituents, referred to as component F of the composition according to the invention, can also be introduced by known methods or in the form of a masterbatch. The use of masterbatches is particularly suitable for the introduction of the additives and further constituents, and masterbatches based on the respective polymer matrix are particularly used.
[0118] The composition according to the invention can be extruded, for example. After extrusion, the extrudate can be cooled and crushed. The premix can also be mixed together in the melt in the plasticizing unit of an injection molding machine. In this case, the melt is directly converted into a molded article in a subsequent step.
[0119] The compositions according to the invention are preferably used for the manufacture of mouldings for components in the EE sector, in particular for high voltage switches, inverters, relays, electronic connectors, electrical connectors, circuit breakers, components for photovoltaic applications, electric motors, heat sinks, chargers and charging plugs for electric vehicles, electrical junction boxes, smart meter housings, miniature circuit breakers, busbars. The invention therefore also provides mouldings which consist of the composition according to the invention or which contain areas made of the composition according to the invention, as well as corresponding parts which comprise elements or mouldings which consist of the composition according to the invention or which contain areas made of the composition according to the invention, which are referred to as "elements made of the thermoplastic composition according to the invention".
[0120] Mouldings consisting of the thermoplastic composition according to the invention or comprising areas made of the thermoplastic composition according to the invention, or layers of the thermoplastic composition according to the invention, are preferably used in EE components designed for a working voltage of at least 400 V, more preferably at least 450 V. However, they can also be designed for 230 V±23 V, typical domestic working voltages in Europe, although a reduction in the conductor distance can be achieved here.
[0121] The high comparative tracking index of the polycarbonate composition according to the invention makes it possible to use this polycarbonate material to reduce the distance between two conductors in a component than was previously possible using polycarbonate.
[0122] Accordingly, the present invention also provides an EE component, comprising a first conductor and a second conductor at a first distance d1 and a second distance d2 relative to each other, These electrical conductors are connected via an element made of a thermoplastic composition according to the invention, which is in direct contact with the first electrical conductor and the second electrical conductor, distance d1 is the shortest distance between the first and second electrical conductors along a surface of the element made of the thermoplastic composition; Distance d2 is the shortest distance between the first conductor and the second conductor through air; d2 is selected to prevent sparks through the air at each operating voltage; d1 is as follows, at the working voltage U listed below: d1i(0V≦U≦250V):1.8mm~<2.5mm d1ii(250V <U≦500V)=3.6mm~<5.0mm d1iii(500V <U≦1000V)=7.1mm~<10.0mm。
[0123] Such short distances are only achievable using materials with a CTI of at least 400V.
[0124] The present invention therefore also provides corresponding EE components, in which the corresponding distances are achieved and in which a working voltage of at least 400V, preferably at least 450V, is preferably applied.
[0125] It is known that the degree of contamination affects the electrical conductivity. The mentioned distances d1 and d2 are practical for example in components complying with the IP6K9K degree of protection according to ISO 20653:2013-02 due to structural shielding.
[0126] The selection of d2 is within the ability of one skilled in the art. Preferably, d2 is at least 1.2 mm.
[0127] The present invention further provides the use of talc to increase the comparative tracking index of bisphenol A homopolycarbonate. Such a specific use exists, for example, when the corresponding composition is used as an insulating layer that requires a CTI of 400V for the application. For example, the composition according to the present invention can be used as an insulating layer for other electrical components, such as transistors. The electrical components of the transistor are protected by overmolding with a plastic having a high CTI. The plastic protects the electrical components from contact and from undesired electrical interaction with adjacent metal components, such as metal heat sinks, or electrical components.
[0128] Due to the high heat generated during operation, transistors are often applied directly to a heat sink, and here too the thermoplastic composition according to the invention introduced between the heat sink and the transistor ensures safe operation.
[0129] A further field of use is mounting brackets for busbars, where again it is necessary to use materials with a high CTI. The mounting brackets have essentially two functions: fixing the busbars in an assembly group to prevent any changes in position during operation, and acting as a spacer to allow several busbars to run in parallel, where again the distance between two busbars must be large enough to prevent sparks through the air. However, in addition, tracking on the surface of the mounting bracket must be prevented, not only between the busbars, but also between the busbars and other metal parts, e.g. the screws for fixing the mounting bracket to the structure below. Mounting brackets with a high CTI can increase the component density and energy density here.
[0130] For plug connectors, plug devices and sockets, there is a high risk of tracking currents occurring, which can lead to electrical failure and possible fires. Enclosures that enclose the current-carrying wires can improve this situation, as they have a lower risk of contamination. Plug connectors for chargers or other USB-C plug connectors have a higher risk, as they cannot cover or enclose the current-carrying conductor tracks and are further exposed to contamination such as sweat, moisture, fabric particles, dust and other substances. High CTI materials are needed to provide sufficient protection from tracking, but also to allow for miniaturization or increased power density.
[0131] The present invention also provides, in the embodiments described as preferred, particularly preferred etc., the use of the compositions according to the invention for achieving the above-mentioned short distances between conductors in EE components.
[0132] Naturally, the features stated as preferred, particularly preferred etc. for the composition also apply in relation to the uses according to the invention.
[0133] Suitable thermoplastic compositions according to the invention belong to insulating material group II (400V≦CTI<600V) according to the classification according to DIN EN 60664-1:2008.
[0134] They preferably have a thermal conductivity (in-plane) of at least 1.0 W / (mK), preferably at least 1.1 W / (mK), as specified according to ASTM E 1461-13, so that good heat dissipation can further be achieved.
[0135] Various embodiments of the present invention are described below:
[0136] 1. A thermoplastic composition comprising: A) at least 50% by weight of bisphenol A homopolycarbonate; B) 32% to 37% by weight of talc; C) 4% by weight to 10% by weight of a phosphorus-containing flame retardant; D) 0.3% by weight to 2% by weight of a fluorine-containing drip prevention agent; E) 1 wt% to 3 wt% of an anhydride-modified α-olefin polymer; and not containing any further filler.
[0137] 2. The thermoplastic composition according to embodiment 1, wherein the talc content of the thermoplastic composition is 34% by weight to 36% by weight.
[0138] 3. The thermoplastic composition according to embodiment 1 or 2, wherein the talc content of the thermoplastic composition is 34.5% by weight to 35.5% by weight.
[0139] 4. The thermoplastic composition according to any of the previous embodiments, wherein the amount of the fluorine-containing anti-drip agent is 0.4 wt.% to 1.0 wt.%.
[0140] 5. A thermoplastic composition according to any of the previous embodiments, wherein the amount of aromatic polycarbonate is at least 54 wt.%.
[0141] 6. A thermoplastic composition according to any of the previous embodiments that does not contain any additional polycarbonate.
[0142] 7. A thermoplastic composition according to any of the previous embodiments, wherein the phosphorus-containing flame retardant is a phosphazene or a mixture of different phosphazenes.
[0143] 8. A thermoplastic composition according to any of the previous embodiments, wherein said anhydride-modified α-olefin polymer comprises, and preferably is, a maleic anhydride-modified propylene polymer.
[0144] 9. A thermoplastic composition according to any of the previous embodiments, wherein the composition contains 0.1% to 2% by weight of titanium dioxide.
[0145] The thermoplastic composition according to any of the previous embodiments, containing 10.5% to 8% by weight of a phosphorus-containing flame retardant.
[0146] 11. Additional ingredients include: F) one or more additives selected from the group consisting of heat stabilizers, antioxidants, release agents, ultraviolet absorbers, infrared absorbers, impact resistance improvers, antistatic agents, fluorescent brighteners, light scattering agents, hydrolysis stabilizers, ester exchange stabilizers, organic dyes, organic or inorganic pigments, compatibilizers, and additives for laser marking; The thermoplastic composition according to any of the previous embodiments,
[0147] 12. A thermoplastic composition according to any of the previous embodiments, wherein the composition does not comprise an impact modifier and a blend partner.
[0148] 13. A) at least 50% by weight of bisphenol A homopolycarbonate; B) 34% to 36% by weight of talc; C) 5% by weight to 8% by weight of a phosphorus-containing flame retardant; D) 0.3% by weight to 1% by weight of a fluorine-containing drip prevention agent; E) 1 wt% to 2 wt% of an anhydride-modified α-olefin polymer; The thermoplastic composition according to any of the previous embodiments,
[0149] 14. F) one or more additives selected from the group consisting of heat stabilizers, antioxidants, release agents, ultraviolet absorbers, infrared absorbers, antistatic agents, fluorescent brighteners, light scattering agents, hydrolysis stabilizers, ester exchange stabilizers, organic dyes, organic or inorganic pigments, compatibilizers, and additives for laser marking; The thermoplastic composition according to any of the previous embodiments, further comprising:
[0150] 15. A thermoplastic composition according to any of the previous embodiments, not containing any additional components other than those mentioned above.
[0151] 16. A thermoplastic composition comprising: A) at least 50% by weight of bisphenol A homopolycarbonate; B) 34% to 36% by weight of talc; C) 5% by weight to 8% by weight of a phosphorus-containing flame retardant; D) 0.3% by weight to 1% by weight of a fluorine-containing drip prevention agent; E) 1 wt% to 2 wt% of an anhydride-modified α-olefin polymer; F) 0.1% by weight to 2% by weight of titanium dioxide; G) one or more additives selected from the group consisting of heat stabilizers, antioxidants, release agents, ultraviolet absorbers, infrared absorbers, antistatic agents, fluorescent brighteners, light scattering agents, hydrolysis stabilizers, ester exchange stabilizers, organic dyes, organic or inorganic pigments, compatibilizers, and additives for laser marking; A thermoplastic composition comprising:
[0152] 17. A thermoplastic composition according to any of the previous embodiments, wherein the phosphorus-containing flame retardant comprises a cyclic phosphazene and / or a phosphorus compound of formula (10).
[0153] 18. The phosphorus-containing flame retardant is a cyclic phosphazene and / or a phosphorus compound of formula (10), TIFF2025512094000009.tif35170 formula, R 1 , R 2 , R 3 , and R4 are independently a C1-C8-alkyl radical, which in each case is optionally halogenated, in each case branched or unbranched, and / or a C5-C6-cycloalkyl radical, a C6-C 20 -aryl radical, or C7-C 12 - aralkyl radicals, which in each case are optionally substituted by branched or unbranched alkyl and / or halogen, preferably chlorine and / or bromine, n is independently 0 or 1; q is a value between 0 and 30; A thermoplastic composition according to any of the previous embodiments, wherein X is a monocyclic or polycyclic aromatic radical having 6 to 30 carbon atoms, or a linear or branched chain aliphatic radical having 2 to 30 carbon atoms, each of which can be substituted or unsubstituted and can be crosslinked or non-crosslinked.
[0154] 19. The cyclic phosphazene is a phosphazene of formula (13): TIFF2025512094000010.tif41170 formula, R is in each case the same or different, is an amine radical, in each case an optionally halogenated, preferably fluorohalogenated, more preferably monohalogenated, C1-C8-alkyl radical, preferably a methyl, ethyl, propyl or butyl radical, a C1-C8 alkoxy radical, preferably a methoxy, ethoxy, propoxy or butoxy radical, in each case optionally alkyl-substituted, preferably C1-C4-alkyl-substituted and / or halogen-substituted, preferably chlorine- and / or bromine-substituted, C5-C6-cycloalkyl radicals, In each case, optionally alkyl-substituted, preferably C1-C4-alkyl-substituted, and / or halogen-substituted, preferably chlorine, bromine, and / or hydroxy-substituted, C6-C 20 an aryloxy radical, preferably a phenoxy radical, a naphthyloxy radical, In each case, optionally alkyl-substituted, preferably C1-C4-alkyl-substituted, and / or halogen-substituted, preferably chlorine- and / or bromine-substituted, C7-C 12 - an aralkyl radical, preferably a phenyl-C1-C4-alkyl radical, or a halogen radical, preferably chlorine or fluorine, or is the OH radical, The thermoplastic composition according to embodiment 17 or 18, wherein k is a natural number from 1 to 10, preferably from 1 to 8, particularly preferably from 1 to 5, and especially preferably 1.
[0155] 20. The phosphorus compound of formula (10) is a bisphenol A-based oligophosphate ester of formula (12), TIFF2025512094000011.tif54170The thermoplastic composition according to embodiment 17, 18 or 19, wherein q=1 to 20, in particular q=1.0 to 1.2.
[0156] 21. The anhydride-modified α-olefin polymers according to component C are based on propene and modified with maleic anhydride, preferably having an average molecular weight M of 1000 g / mol to 22000 g / mol, preferably 3000 g / mol to 21000 g / mol, as determined by gel permeation chromatography at 150° C. in orthodichlorobenzene using polystyrene calibration. w and an acid number, determined by potentiometric titration according to DIN ISO 17025:2005-08, of 45 mg KOH / g to 170 mg KOH / g, preferably of 50 mg KOH / g to 100 mg KOH / g.
[0157] 22. The MVR of the aromatic bisphenol A homopolycarbonate used is specified in accordance with ISO 1133:2012-03 at a test temperature of 300°C and a load of 1.2 kg, and 3 / (10 minutes)~15cm 3 22. The thermoplastic composition according to embodiment 21, wherein:
[0158] 23. A molding comprising a region consisting of or made of a thermoplastic composition according to any of the previous embodiments.
[0159] 24. The molding according to embodiment 23, wherein the molding is part of a high voltage switch, an inverter, a relay, an electronic connector, an electrical connector, a circuit breaker, a photovoltaic power generation system, an electric motor, a heat sink, an electric vehicle charger or charging plug, an electrical junction box, a smart meter housing, a miniature circuit breaker, or a busbar.
[0160] 25. An EE part designed for a working voltage of at least 375 V, comprising a layer made of a molding according to embodiment 23 or 24, or a thermoplastic composition according to any of embodiments 1 to 22.
[0161] 26. An EE part designed for a working voltage of 400 V, comprising a layer made of a molding according to embodiment 23 or 24 or a thermoplastic composition according to any of embodiments 1 to 22.
[0162] 27. An EE part, a first conductor and a second conductor at a first distance d1 and a second distance d2 from each other; Including, They are connected via an element made of a thermoplastic composition according to any one of embodiments 1 to 22, which is in direct contact with the first and second electrical conductors; distance d1 is the shortest distance between the first and second electrical conductors along a surface of the element made of the thermoplastic composition; Distance d2 is the shortest distance between the first conductor and the second conductor through air; d2 is selected to prevent sparks through the air at each operating voltage; d1 is the following at the working voltage U listed below: d1i(0V≦U≦250V):1.8mm~<2.5mm d1ii(250V <U≦500V)=3.6mm~<5.0mm d1iii(500V <U≦1000V)=7.1mm~<10.0mm That is, EE parts.
[0163] 28. An EE part according to any one of embodiments 25 to 27, wherein d2 is 1.2 mm or more.
[0164] 29. The EE part according to any of embodiments 25 to 28, which is a high voltage switch, an inverter, a relay, an electronic connector, an electrical connector, a circuit breaker, part of a solar power generation system, part of an electric motor, part of a charger and a charging plug for an electric vehicle, part of an electrical junction box, part of a smart meter housing, part of a miniature circuit breaker, or part of a busbar.
[0165] 30. An EE part according to any of embodiments 25 to 30, having an IP6K9K degree of protection according to ISO 20653:2013-02. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES
[0166] 1. Description of raw materials and testing methods a) Raw materials Component A-1: A linear polycarbonate based on bisphenol A, which has a melt volume flow rate of 12 cm 3 / (10 min) (in accordance with ISO 1133:2012-03 at a test temperature of 300° C. and a load of 1.2 kg) and contains 250 ppm (=0.025% by weight, based on the total weight of component A) of triphenylphosphine heat stabilizer as component F-2.
[0167] Component B-1: Compressed talc, which has a talc content of 98% by weight, an iron oxide content of 1.9% by weight, an aluminum oxide content of 0.2% by weight, an ignition loss of 5.4% by weight (DIN 51081:2002 / 1000°C), a pH of 9.15 (according to EN ISO 787-9:1995), a D(0.5) of 2.2 μm (sedimentation analysis), a viscosity of 10 m 2 / g BET surface area according to ISO 4652:2012-06, trade name: Finntalc M05SLC, manufacturer: Elementis Minerals BV.
[0168] Component B * -2: Glass fiber from Nitto Boseki Co., Ltd. (2-4-1 Kojimachi, Chiyoda-ku, Tokyo 102-8489, Japan) available under the trade name CSG 3PA-830. This is a flat glass fiber with a cut length of 3 mm and a cross-sectional area ratio of 1.4.
[0169] Component B * -3: Amosil FW 600 calcined silicon dioxide from Quarzwerke GmbH, Frechen, which is unsized and has an average particle size D(0.5) of about 4 μm, a D(0.98) of about 13 μm, a D(0.1) / D(0.9) ratio of about 1.5 / 10, and a pore size (pore diameter) of about 6 μm as specified according to DIN-ISO 9277:2014-01. 2 / g.
[0170] Component C-1: Rabitle FP110 phenoxycyclophosphazene, manufactured by Fushimi Pharmaceutical Co., Ltd. (Japan), formula (13g), trimer ratio (k=1) is approximately 68 mol%.
[0171] Component D-1: ADS5000 SAN encapsulated polytetrafluoroethylene (approximately 50% by weight PTFE (a fluorine-containing anti-drip agent) and approximately 50% by weight SAN), manufactured by Chemical Innovation Co., Ltd. Thailand.
[0172] Component E-1: Propylene-maleic anhydride polymer, which has an average molecular weight (gel permeation chromatography in orthodichlorobenzene at 150° C. with polystyrene calibration) M w = 20700 g / mol, M n = 1460 g / mol, and an acid number determined by potentiometric titration according to DIN ISO 17025:2005-08 of 78 mg KOH / g.
[0173] Ingredient F-1: Titanium dioxide from Kronos, which is D 50 = 210 nm (scanning electron microscopy, ECD method; Kronos™ 2230).
[0174] b) Test method Comparative Tracking Index (CTI): For the purpose of determining the comparative tracking index, the compositions described herein were tested according to the rapid test method according to IEC 60112:2009. For this purpose, a 0.1% ammonium chloride test solution (395 ohm·cm resistivity) was dropped onto the surface of a test specimen with dimensions 60 mm×40 mm×4 mm, between two adjacent electrodes spaced 4 mm apart, with a time interval of 30 seconds. A test voltage was applied between the electrodes and varied over the course of the test. The first test specimen was tested with a starting voltage of 300 V or 350 V. A maximum of 50 drops in total per voltage (one drop every 30 seconds) were dropped as long as no tracking current of more than 0.5 A occurred for 2 seconds or the specimen did not burn. After 50 drops, the voltage was increased by 50 V and a new specimen was tested at this increased voltage according to the procedure described above. This process continued until either 600 V was reached or a tracking current or burning occurred. If one of the above effects occurred already in less than 50 drops, the voltage was reduced by 25V and a new specimen was tested at this reduced voltage. The voltage was reduced until the test completed 50 drops without causing tracking current or burning. Thus, this procedure was used to identify the maximum possible voltage at which the composition could withstand 50 drops of test solution without causing tracking current. Finally, for confirmation, four more specimens were tested with 50 drops each at the maximum voltage specified. This confirmed value was reported as the CTI in the examples. The 100 drop value was not specified because it was a "rapid test method based on" the specified standard.
[0175] PTI (Guaranteed Tracking Index): PTI is tested according to IEC 60112:2009 with the following modifications. For this purpose, a 0.1% ammonium chloride test solution (395 ohm cm resistivity) is dropped onto the surface of a specimen with dimensions 60 mm x 40 mm x 4 mm, between two adjacent electrodes spaced 4 mm apart, with a time interval of 30 seconds. In contrast to the CTI test, in the PTI test a constant test voltage is applied between the electrodes, and a total of five specimens are tested at each voltage. A maximum of 50 drops in total (one drop every 30 seconds) are dropped per specimen, as long as no tracking current of more than 0.5 A occurs for 2 seconds or the specimen does not burn.
[0176] Flame Retardant: The flame retardancy of the polycarbonate compositions was tested according to Underwriters Laboratories method UL94V at a thickness of 2 mm.
[0177] Depending on the behavior of the specimens, they are assigned to various flammability classes, including time to flame extinguish, drip resistance, or whether the material produces flammable drips. Hereinafter, the identified classes will be designated V0, V1, and V2. These are established based on a total of five specimens tested.
[0178] V0: A specimen that, when placed at 180° (perpendicular) with its long axis to the flame, has an average afterflame time of 10 seconds or less after the flame is removed and does not produce any drips of plastic particles that ignite cotton wool placed under the specimen. The total afterflame time with two applications of the flame to each of the five specimens is a maximum of 50 seconds.
[0179] V1: In contrast to V0, the average maximum afterflame time in this case is less than 30 seconds, but again no ignition of dripping particles or cotton wool is permitted. The total afterflame time with two flame applications to each of the five specimens is less than 250 seconds.
[0180] V2: In contrast to V0 and V1, this classification results in the formation of drips of plastic particles which ignite the cotton wool. The individual afterflame times are less than 30 seconds and the total afterflame time of two flame applications to each of the five specimens is less than 250 seconds.
[0181] f.: If the afterflame time exceeds the above, this test does not assign a flame retardant classification.
[0182] FOT: Flame out time (afterflame time), reported in seconds.
[0183] Heat Distortion Resistance: The heat distortion resistance of the compositions was determined on test specimens with dimensions 80 mm x 10 mm x 4 mm based on the Vicat softening temperature (Method B, test force 50 N, heating rate 50 K / h) according to ISO 306:2014-3.
[0184] Thermal Conductivity: Thermal conductivity is measured according to ASTM E 1461 (Nano Flash method) for a 60 x 60 x 2 mm 3 The properties were determined on injection molded specimens of 0.01 mm in diameter. "In-plane" means measurements in the x,y directions, and "normal" means measurements in the z direction.
[0185] 2. Preparation of Test Specimens The compositions were prepared in a BUSS kneader. Melt temperature, rotation speed, throughput and torque had to be adjusted for each composition, according to procedures known to those skilled in the art. The fillers were metered in as a "split-feed", with 10% by weight of the total filler added through the main intake and the rest through a side extruder. Test pieces with dimensions 60 mm x 40 mm x 4 mm were produced from the molding compounds using standard injection molding techniques, with a melt temperature of 280°C and a mold temperature of 80°C.
[0186] 3.Results In the table below, "nt" means "not tested" and "f." means "failed."
[0187] [Table 1]
[0188] Table 1 shows a tendency for the CTI to improve with increasing talc content (V-1 to V-3). However, without the addition of flame retardant, flammability increases with increasing talc content (see afterflame time). Comparing examples V-4, E-7 and V-11, each containing 5% by weight of flame retardant, the tendency for the CTI to increase with increasing talc content (325V-450V-500V) can be seen here as well. It is necessary to use no more than 10% by weight of flame retardant, preferably no more than 8% by weight, so that the heat distortion resistance is not so greatly reduced that the use of polycarbonate in general is called into question. Other reinforcing fillers such as glass fiber or quartz cannot achieve such high comparative tracking indexes as talc in combination with FR packages (see V2 vs. V-9 and V-10).
Claims
1. 1. A thermoplastic composition comprising: A) at least 50% by weight of bisphenol A homopolycarbonate; B) 32% to 37% by weight of talc; C) 4% to 10% by weight of a phosphorus-containing flame retardant; D) 0.3% to 2% by weight of a fluorine-containing anti-drip agent; E) 1 wt % to 3 wt % of an anhydride modified α-olefin polymer; and not containing any further filler.
2. 10. The thermoplastic composition of claim 1 which does not contain any additional polycarbonate.
3. The thermoplastic composition of claim 1 or 2, containing 5% to 8% by weight of a phosphorus-containing flame retardant.
4. The thermoplastic composition of any one of claims 1 to 3, wherein the anhydride modified α-olefin polymer comprises a maleic anhydride modified propylene polymer.
5. The thermoplastic composition according to any one of claims 1 to 4, containing from 34% to 36% by weight of talc.
6. As a further ingredient, F) one or more additives selected from the group consisting of heat stabilizers, antioxidants, release agents, ultraviolet absorbers, infrared absorbers, impact resistance improvers, antistatic agents, fluorescent brighteners, light scattering agents, hydrolysis stabilizers, ester exchange stabilizers, organic dyes, organic or inorganic pigments, compatibilizers, and additives for laser marking; The thermoplastic composition according to any one of claims 1 to 5, comprising:
7. A thermoplastic composition according to any one of claims 1 to 6, containing from 0.1% to 2% by weight of titanium dioxide.
8. A) at least 50% by weight of bisphenol A homopolycarbonate; B) 34% to 36% by weight of talc; C) 5% to 8% by weight of a phosphorus-containing flame retardant; D) 0.3 wt.% to 1 wt.% of a fluorine-containing anti-drip agent; E) 1% to 2% by weight of an anhydride modified α-olefin polymer; The thermoplastic composition according to any one of claims 1 to 7, comprising:
9. F) one or more additives selected from the group consisting of heat stabilizers, antioxidants, release agents, ultraviolet absorbers, infrared absorbers, antistatic agents, fluorescent brighteners, light scattering agents, hydrolysis stabilizers, ester exchange stabilizers, organic dyes, organic or inorganic pigments, compatibilizers, and additives for laser marking; 9. The thermoplastic composition of claim 8, further comprising: 0.1% to 2% by weight of titanium dioxide is present.
10. The thermoplastic composition according to any one of claims 1 to 9, which does not contain any further components other than those mentioned above.
11. A molding consisting of the thermoplastic composition according to any one of claims 1 to 10 or comprising a region made of the thermoplastic composition according to any one of claims 1 to 10.
12. The molding according to claim 11, wherein the molding is part of a high voltage switch, inverter, relay, electronic connector, electrical connector, circuit breaker, photovoltaic system, electric motor, heat sink, electric vehicle charger and charging plug, electrical junction box, smart meter housing, miniature circuit breaker, busbar, and the EE part preferably has a degree of protection IP6K9K according to ISO 20653:2013-02.
13. EE part comprising a moulding according to claim 11 or 12 or a layer made of the thermoplastic composition according to any one of claims 1 to 10.
14. a first conductor and a second conductor at a first distance d1 and a second distance d2 from each other; Including, They are connected via the thermoplastic composition according to any one of claims 1 to 10, the thermoplastic composition being in direct contact with the first electrical conductor and the second electrical conductor; the distance d1 is the shortest distance between the first electrical conductor and the second electrical conductor along a surface of the thermoplastic composition; the distance d2 is the shortest distance between the first conductor and the second conductor through air, d2 is selected to prevent sparks through the air at each operating voltage; d1 is, at the working voltage U listed below, d1i (0V≦U≦250V): 1.8mm~<2.5mm d1i (250V<U≦500V)=3.6mm~<5.0mm d1iii (500V<U≦1000V)=7.1mm~<10.0mm EE part according to claim 13,
15. Use of talc to enhance the comparative tracking index of a bisphenol A homopolycarbonate based thermoplastic composition.
Citation Information
Patent Citations
Polycarbonate composition comprising talc
WO2018037037A1
Heat-conducting polycarbonates having improved flame protection by means of barium sulfate
WO2020212245A1